2012
DOI: 10.1364/ao.51.00c198
|View full text |Cite
|
Sign up to set email alerts
|

High-intensive femtosecond singular pulses in Kerr dielectrics

Abstract: The nonlinear dynamics of a high-power femtosecond singular pulse in Kerr media are analyzed numerically upon optically induced ionization. We examine the plasma inertia impact to stable propagation of optical vortices. Multifoci behavior of vortices in medium are revealed. Next we numerically demonstrate that inertial character of plasma formation provides a quasi-soliton regime of vortex propagation resistant to symmetry-breaking perturbation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…Being interested in the stable propagation of the pulsed vortex beams in the medium, we search for the soliton or, at least, quasi-soliton solutions. As earlier shown in the work [8], the competition of the Kerr focusing and the defocusing plasma nonlinearities can provide quasisoliton regime of the vortex propagation under negligible effect of the GVD. Fig.…”
Section: Two-scale Variational Approachsupporting
confidence: 58%
See 3 more Smart Citations
“…Being interested in the stable propagation of the pulsed vortex beams in the medium, we search for the soliton or, at least, quasi-soliton solutions. As earlier shown in the work [8], the competition of the Kerr focusing and the defocusing plasma nonlinearities can provide quasisoliton regime of the vortex propagation under negligible effect of the GVD. Fig.…”
Section: Two-scale Variational Approachsupporting
confidence: 58%
“…It should be noted that inclusion of the GVD makes possible pulse refocusing for larger ratios  than those typical for the case when the dispersion is completely absent [8]. We would recall in this respect that the multifoci scenario observed in our previous work takes place at  =15.57 or even smaller values.…”
Section: Two-scale Variational Approachmentioning
confidence: 65%
See 2 more Smart Citations
“…Moreover, numerical investigations have shown that the nonlocality of nonlinear medium plays the key role in the stabilization of the propagation of singular beams of specific type [21][22][23]. The interest to the processes accompanying the filamentation of singular beams also increases [24,25].…”
Section: Introductionmentioning
confidence: 99%